Novel agonists for serotonin 5-HT7 receptors reverse metabotropic glutamate receptor-mediated long-term depression in the hippocampus of wild-type and Fmr1 KO mice, a model of Fragile X Syndrome - Costa, Lara; Sardone, Lara M.; Lacivita, Enza; Leopoldo, Marcello; Ciranna, Lucia (Frontiers in Behavioral Neuroscience, 2015)
Serotonin 5-HT7 receptors are expressed in the hippocampus and modulate the excitability of hippocampal neurons. We have previously shown that 5-HT7 receptors modulate glutamate-mediated hippocampal synaptic transmission and long-term synaptic plasticity. In particular, we have shown that activation of 5-HT7 receptors reversed metabotropic glutamate receptor-mediated long-term depression (mGluR-LTD) in wild-type (wt) and in Fmr1 KO mice, a mouse model of Fragile X syndrome in which mGluR-LTD is abnormally enhanced, suggesting that 5-HT7 receptor agonists might be envisaged as a novel therapeutic strategy for Fragile X syndrome. In this perspective, we have characterized the basic in vitro pharmacokinetic properties of novel molecules with high binding affinity and selectivity for 5-HT7 receptors and we have tested their effects on synaptic plasticity using patch clamp on acute hippocampal slices. Here we show that LP-211, a high affinity selective agonist of 5-HT7 receptors, reverses mGluR-LTD in wt and Fmr1 KO mice, correcting a synaptic malfunction in the mouse model of Fragile X syndrome. Among novel putative agonists of 5-HT7 receptors, the compound BA-10 displayed improved affinity and selectivity for 5-HT7 receptors and improved in vitro pharmacokinetic properties with respect to LP-211. BA-10 significantly reversed mGluR-LTD in the CA3-CA1 synapse in wt and Fmr1KO mice, indicating that BA-10 behaved as a highly effective agonist of 5-HT7 receptors and reduced exaggerated mGluR-LTD in a mouse model of Fragile X Syndrome. On the other side, the compounds RA-7 and PM-20, respectively arising from in vivo metabolism of LP-211 and BA-10, had no effect on mGluR-LTD thus did not behave as agonists of 5-HT7 receptors in our conditions. The present results provide information about the structure-activity relationship of novel 5-HT7 receptor agonists and indicate that LP-211 and BA-10 might be used as novel pharmacological tools for the therapy of Fragile X syndrome.